The role of psychological distance in organizational responses to modern slavery risk in supply chains. Issue 8 (24th September 2021) - Simpson, Dayna; Segrave, Marie; Quarshie, Anne; Kach, Andrew; Handfield, Robert; Panas, George; Moore, Heather
Abstract: Modern slavery is used to describe forms of coercive labor exploitation that affect more than 40 million persons globally. Such practices are difficult to identify given they exist in the informal economy, and involve vulnerable individuals. Addressing modern slavery by organizations requires awareness of its context and complexities. While corporations have increasingly sought to manage modern slavery risk in their supply chains, their understanding of what modern slavery is and what should be managed remains limited. We argue a key problem with firms' efforts to manage modern slavery risk is that it is a psychologically distant concept for them. We apply construal level theory to explore how organizations' psychological distance from modern slavery risk affects their management of risk. We interviewed purchasing executives at 41 global organizations in Australia, Finland, and the U.S and identified four approaches to managing modern slavery risk at different levels of psychological distance. We also identified that conflicts between organizations' approaches to risk and what they identify in their operating environment, precedes important construal shifts that help to improve organizational understanding of labor‐related risk. We highlight ways that organizations' understanding of modern slavery risk plays a role in their governance of such risk in supply chains.